Expecting the unexpected in Whipple procedures: A series of unusual conditions mimicking periampullary carcinoma - Nichat, Prachi; Rana, Vandana; Bharathi, Saranga; Mishra, Abhishek (Journal of Pathology of Nepal, 2025)
Benign diseases centered around periampullary/ pancreatic head region may mimic malignancy sharing similar clinico-radiologic features. Thereby create grounds for surprises on pathologic examination.Cases of pancreatoduodenectomy performed for suspected malignancy between Aug 2022-Aug 2023 at a low volume tertiary centre were retrospectively audited for discrepancy between pre-operative and final histopathologic diagnosis. Nine pancreatoduodenectomies were performed, of which 6 turned out to be malignant and 3, unexpectedly turned out to be benign: 1 case each of adenomyomatous hyperplasia of the ampulla of Vater, autoimmune pancreatitis- II, and eosinophilic ampullitis.There remains a clear and ever-present probability of encountering rare unexpected benign pathology in pancreas specimen resected suspecting malignancy. Ambiguous cases might benefit from further investigation to avoid morbid resectional surgery.